2018
DOI: 10.1002/nop2.133
|View full text |Cite
|
Sign up to set email alerts
|

Nurse education and understanding related to domestic violence and abuse against women: An integrative review of the literature

Abstract: AimThe aim of this study was to explore previous literature related to nurses understanding of Intimate partner violence (IPV) or domestic violence and abuse (DVA) against women and to identify the gaps in nursing education so as to use the findings as a baseline to inform potential intervention strategies, curriculum development and outline implications for future nursing practice.DesignAn Integrative review of literature.MethodsStudies were extracted through a search of the electronic databases, such as Scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
0
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 40 publications
7
42
0
12
Order By: Relevance
“…This is consistent with the findings of other studies (18)(19)(20)(21)(22)(23)26). On the other hand, an American study found those two barriers were reported by only 9.4% of their participants (27).…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with the findings of other studies (18)(19)(20)(21)(22)(23)26). On the other hand, an American study found those two barriers were reported by only 9.4% of their participants (27).…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the importance of including education related to domestic abuse in undergraduate health professional programmes (highlighted in research by Eustace (2016) as being minimal) has been suggested as a key feature in ensuring that health professionals are prepared for disclosure in their professional lives (Alshammari et al, 2018). Undergraduate training programmes present an ideal opportunity to raise the awareness of future registered health professionals about domestic abuse (DH, 2017), but it is currently not clear how this is being addressed in such programmes nationally.…”
Section: Discussionmentioning
confidence: 99%
“…Domestic abuse is recognised as having significant longterm health implications, both physically and psychologically, including post-traumatic stress disorder, depression and anxiety (Chambliss, 2008;Cunningham, 2008;Sarker, 2008;Cerulli et al, 2012). Moreover, the NHS is identified as often being the first point of contact for women suffering from domestic abuse (Alshammari et al, 2018, IRIS, 2020. Such women often have a higher rate of contact with health professionals than other women (Plichta, 2007), reporting that they consider health professionals as people whom they trust most to disclose abuse to (WHO, 2013).…”
Section: Nice 2016amentioning
confidence: 99%
“…In order for nurses to screen for IPV and appropriately respond to survivors, it is important for nurses to receive adequate and effective IPV education and training (Anderzen‐Carlsson et al, 2018), as well as well‐designed “prequalification” healthcare provider training (i.e., for students) (Crombie et al, 2017; WHO, 2013). However, nursing education is often quite inadequate related to IPV (Alshammari et al, 2018; Bradbury‐Jones & Broadhurst, 2015; Doran & Hutchinson, 2017) and nursing students lack knowledge and confidence to address IPV in practice, talk to IPV survivors, or effectively assist or empathise with them (Bradbury‐Jones & Broadhurst, 2015; Doran & Hutchinson, 2017; Thornton & Persuad, 2017). Further, systematic evaluations of the impact or effectiveness of IPV education and training administered in nursing schools are relatively rare.…”
Section: Introductionmentioning
confidence: 99%